When Minutes Fly by: What is the True "Golden Hour" for Air Care?. Issue 6 (June 2018) - Duke, Marquinn; Tatum, Danielle; Sexton, Kevin; Stuke, Lance; Robertson, Ronald; Sutherland, Michael; Tyroch, Alan; Agrawal, Vaidehi; Duchesne, Juan
Air transport was developed to hasten patient transport based on the "golden hour" belief that delayed care leads to poorer outcome. The primary aim of our study was to identify the critical inflection point of increased nonsurvivors on total prehospital time. This was a multicenter review of adult trauma patients transported by air between November 2014 and August 2015. Primary outcome of interest was all-cause inhospital mortality. Total helicopter emergency medical services times of nonsurvivors were plotted to visualize the distribution of prehospital time. Of 636 patients included, 71 per cent were male and 86 per cent suffered blunt trauma. Among non-survivors, mortality doubled once total helicopter emergency medical services time exceeded 30 minutes (P < 0.001). Nonsurvivors presented with significantly lower median [interquartile range (IQR)] Glasgow Coma Score compared with survivors [3 (3–13) vs 15 (12–15), respectively; P < 0.001] as well as a significantly higher median (IQR) Injury Severity Score [26 (19–41) vs 12 (5–22); P < 0.001], increased incidence of penetrating mechanism of injury [21 vs 8%; P = 0.002], and higher median (IQR) shock index [0.84 (0.63–1.06) vs 0.71 (0.6–0.87); P = 0.023]. We identified an inflection point of doubling in mortality after 30 minutes. This suggests a possible threshold effect between time and mortality in severely injured patients. Revised field criteria for determining which injured patients would most benefit from helicopter transport are needed.